Comparison of topical and infiltration anesthesia for orthodontic mini-implant placement - Matheus Miotello Valieri; Karina Maria Salvatore de Freitas; Fabricio Pinelli Valarelli; Rodrigo Hermont Cançado (Dental Press Journal of Orthodontics, 2014)
Objective: To compare the acceptability and effectiveness of topical and infiltration anesthesia for placement of mini-implants used as temporary anchorage devices. Methods: The sample comprised 40 patients, 17 males and 23 females, whose mean age was 26 years old and who were all undergoing orthodontic treatment and in need for anchorage reinforcement. Mini-implants were bilaterally placed in the maxilla of all individuals, with infiltration anesthesia on one side and topical anesthesia on the other. These 40 patients completed two questionnaires, one before and another after mini-implant placement and pain was measured through a visual analog scale (VAS). The data collected were analyzed using descriptive statistics and the measurements of pain were compared by means of the non-parametric test of Mann-Whitney. Results: It was found that 60% of patients felt more comfortable with the use of topical anesthesia for mini-implant placement; 72.5% of patients described the occurrence of pressure during placement of the anchorage device as the most unpleasant sensation of the entire process; 62.5% of patients felt more pain with the use of topical anesthesia. Conclusion: It was concluded that patients had less pain with the use of infiltration anesthesia, and also preferred this type of anesthetic.